Surface Water as an Initial Proton Source for the Electrochemical CO Reduction Reaction on Copper Surfaces. (8th December 2022) - Shao, Feng; Xia, Zhaoming; You, Futian; Wong, Jun Kit; Low, Qi Hang; Xiao, Hai; Yeo, Boon Siang
Abstract: We have employed in situ electrochemical shell‐isolated nanoparticle‐enhanced Raman spectroscopy (SHINERS) and density functional theory (DFT) calculations to study the CO reduction reaction (CORR) on Cu single‐crystal surfaces under various conditions. Coadsorbed and structure‐/potential‐dependent surface species, including *CO, Cu−Oad, and Cu−OHad, were identified using electrochemical spectroscopy and isotope labeling. The relative abundance of *OH follows a "volcano" trend with applied potentials in aqueous solutions, which is yet absent in absolute alcoholic solutions. Combined with DFT calculations, we propose that the surface H2 O can serve as a strong proton donor for the first protonation step in both the C1 and C2 pathways of CORR at various applied potentials in alkaline electrolytes, leaving adsorbed *OH on the surface. This work provides fresh insights into the initial protonation steps and identity of key interfacial intermediates formed during CORR on Cu surfaces. Abstract : Electroreduction of CO on Cu single‐crystal surfaces was investigated with in situ electrochemical shell‐isolated nanoparticle‐enhanced Raman spectroscopy (SHINERS) and density functional theory (DFT). Direct spectroscopic evidence for surface *CO, Cu−Oad, and Cu−OHad species was observed and confirmed with isotopic experiments. Surface *H2 O is the dominant proton source for the initial protonation steps in alkaline electrolytes (pH=13).